Self psychology and psychosis : the development of the self during intensive psychotherapy of schizophrenia and other psychoses - Garfield, David A. S.; Steinman, Ira (Karnac Books, 2015)
In this groundbreaking volume, David Garfield and Ira Steinman bring us into the immediacy of the analyst's consulting room in direct confrontation with the thought disorder, delusions and hallucinations of their patients grappling with psychosis. From the early days of psychoanalysis when Freud explicated the famous Schreber case, analysts of all persuasions have brought a variety of theories to bear on the problem of schizophrenia and the other psychoses. Here, as William Butler Yeats notes, "the centre cannot hold" and any sense of self-esteem - positive feelings about oneself, a continuous sense of self in time and a functional coherence and cohesion of self - is shattered or stands in imminent danger. What makes psychoanalytic self psychology so compelling as a framework for understanding psychosis is how it links together the early recognition of narcissistic impairment in these disorders to the "experience-near" focus which is the hallmark of self psychology. Now, with Garfield and Steinman's descriptions of healing in the mirroring, idealizing and twinship experiences of treatment, the theory of self psychology, in a comprehensive fashion, is brought to bear on the psychoses for the very first time. Join Garfield and Steinman as they bring the reader into these analytic journeys, inspired by Kohut and his followers and crafted with their own original insights as patients find their way back to a meaningful and functional existence